2022
DOI: 10.1111/hsc.13773
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a healthy lifestyle program in residential out‐of‐home care: What matters, what works and what translates?

Abstract: The Healthy Eating, Active Living Matters (HEALing Matters) program is being scaled up across residential out-of-home care (OOHC) in Victoria, Australia and is providing young people with the knowledge, skills and resources to promote better health through healthy eating and activity. HEALing Matters was piloted as the HEAL program, a dual-intervention program that aimed to provide young people living in residential care with education and opportunities to improve their eating and physical activity habits, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This research has shown the positive associations between responsive caregiving and child growth and development (Bethell et al, 2017 ). This is demonstrated, for example, in our multi‐sectoral Healthy Eating Active Living (HEALing) Matters Program for children living in out‐of‐home care (sometimes referred to as looked‐after children; Green et al, 2022 ). HEALing Matters is underpinned by the ethos that the home environment, and the interpersonal relationships that exist between children and their caregivers, are crucial to initiating and maintaining healthy behaviours.…”
Section: Unpacking the “Why”: The Importance Of Supporting A Nurturin...mentioning
confidence: 99%
“…This research has shown the positive associations between responsive caregiving and child growth and development (Bethell et al, 2017 ). This is demonstrated, for example, in our multi‐sectoral Healthy Eating Active Living (HEALing) Matters Program for children living in out‐of‐home care (sometimes referred to as looked‐after children; Green et al, 2022 ). HEALing Matters is underpinned by the ethos that the home environment, and the interpersonal relationships that exist between children and their caregivers, are crucial to initiating and maintaining healthy behaviours.…”
Section: Unpacking the “Why”: The Importance Of Supporting A Nurturin...mentioning
confidence: 99%
“…In addition, previous studies have shown that obese adults perceive eating out as a key barrier to sustained adherence to a specific dietary regime [36]. Therefore, modifying this parameter may be a reasonable strategy to promote healthy eating patterns and prevent weight gain [37]. However, in order to build a scientific case for action and develop appropriate public health strategies, a comprehensive understanding of the specifics of eating out and how they relate to diet quality is needed in the future [35].…”
Section: Comparison With Previous Researchmentioning
confidence: 99%